2013
DOI: 10.1021/jp311707e
|View full text |Cite
|
Sign up to set email alerts
|

What Are Functional Ionic Liquids for the Absorption of Acidic Gases?

Abstract: As a kind of novel and efficient material, ionic liquids (ILs) are used for capture of acidic gases including SO2 and CO2 from flue gas. Due to very low content of acidic gases in flue gas, it is important to find functional ILs to absorb the acidic gases. However, up to now, there is no criterion to distinguish if the ILs are functional or not before use, which greatly influences the design of functional ILs. In this work, a series of ILs were synthesized and used to determine functional or normal ILs for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
69
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 39 publications
1
69
0
Order By: Relevance
“…They are promising alternative absorbents for gas separation [8][9][10][11][12]. ILs exhibit negligible measurable vapor pressure, wide liquid temperature range, and high thermal stability at normal operating conditions, which make them attractive for gas processing [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…They are promising alternative absorbents for gas separation [8][9][10][11][12]. ILs exhibit negligible measurable vapor pressure, wide liquid temperature range, and high thermal stability at normal operating conditions, which make them attractive for gas processing [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, the absorption capacity of SO 2 using [TEOA][CA] was up to 3.34, a three-fold increase over the other ILs. This value was much higher than those of the other hydroxyl ammonium ILs, guanidinium based ILs11,29,33 and azole based ILs18,32,34 at low SO 2 partial pressure. However, the absorption capacity of[TEOA][CA] at low SO 2 partial pressure was lower than those for some ILs with pure SO 2 , such as [TMG]2 [PBE] (8.74 mol/mol)14 and E 3 [Tetz] (4.43 mol/mol) 20.…”
mentioning
confidence: 69%
“…It is found that imidazolium ionic liquids have a certain ability to absorb NO2 gas, but the higher viscosity of ionic liquids (for example,BMIMBF4, 25 ℃ and 110.308 cp) [5]. In order to reduce the viscosity of the ionic liquid and further improve the absorption of NO2 gas, we have studied a series of organic alkali and ionic liquid composite absorption system, after a lot of experiments, we found that the imidazole ionic liquid and N-alkyl imidazole organic alkali prepared by an ionic liquid composite material not only has high absorption capacity, but also has obvious synergistic absorption effect.…”
Section: Absorption Of No2mentioning
confidence: 99%